2006
DOI: 10.1021/jp057094p
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Spectra, Photophysical Properties, and Redox Behavior of Ruthenium(II) Polypyridine Complexes Containing Accessory Dipyrromethene−BF2Chromophores

Abstract: The six multichromophoric species 1-6, containing the potentially luminescent Ru(II) polypyridine subunits and 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene fluorophores (dipyrromethene-BF(2) dyes, herein after called bodipy), have been prepared and their absorption spectra, luminescence properties (both at room temperature in fluid solution and at 77 K in rigid matrix), and redox properties have been investigated (for the structuralformulas of all the compounds, see Figure 1). For comparison purposes, also the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
144
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(159 citation statements)
references
References 38 publications
11
144
1
3
Order By: Relevance
“…Their molecular structures were unambiguously assigned by using 1 H, 13 C, 19 F and 11 B NMR spectroscopy, electrospray mass spectrometry and elemental analysis. Both dyads analysed by ESI-MS gave an intense molecular peak with the expected isotopic profile corresponding to the loss of two PF 6 -counter anions assigned to a doubly charged species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their molecular structures were unambiguously assigned by using 1 H, 13 C, 19 F and 11 B NMR spectroscopy, electrospray mass spectrometry and elemental analysis. Both dyads analysed by ESI-MS gave an intense molecular peak with the expected isotopic profile corresponding to the loss of two PF 6 -counter anions assigned to a doubly charged species.…”
Section: Methodsmentioning
confidence: 99%
“…The oxidation peak at +1.09 V is assigned to the formation of a Bodipy + (BD + ) unit; the irreversibility is also known for other polypyridyl-containing Bodipy molecules. 12,13 The quasireversible wave seen at -1.15 V is associated with the addition of one electron to the Bodipy site.…”
Section: Methodsmentioning
confidence: 99%
“…The other absorption bands of the ligands are due to various - * and - * transitions [5,14,27,29]. In the UV-vis absorption spectra of complexes and the bands at 322, 332, and 323 nm should receive a dominant contribution from transition involving the ligands 3a, 3d, 3e, respectively [6,14,28]. In particular, the bands with 290-300 nm range should receive a dominant contribution from - * transition involving bpy and phen moieties [7,[31][32][33].…”
Section: Uv-vis Absorption and Emission Spectral Studymentioning
confidence: 99%
“…The polypyridine complexes of Ru(II) have been studied extensively with the point of interest being their rich and well characterized photophysics [6,7]. In recent years, transition metal complexes have been used extensively in the fore front of fields such as probes of DNA structure, DNAdependent electron transfer, and site-specific DNA cleavage [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The optical properties of boron diketonate such as its large Stokes shift and two-photon absorption cross sections and the versatile applications based on the incorporation to various organic backbones provide its potential usefulness for a molecular probe, 5 laser, 6 and optical sensing applications. 7,8 Research by Fraser et al on the applications to polymeric materials has reported synthesis of boron diketonate-containing polylactide and the oxygen-sensing property. 9 Moreover, Chujo et al have demonstrated synthesis and emission color-tunings of the main chain-type poly(boron diketonate)s. [10][11][12] However, the synthetic difficulty of the boron diketonate-containing polymers restricts applicability of the polymer.…”
Section: Introductionmentioning
confidence: 99%